The Awareness and willingness to apply for halal guarantee certification: a study of MSMEs assisted by BAZNAS Yogyakarta - Ikawati, Retty; Rahman, Anisa Nur Baiti (Journal of Halal Science and Research, 2022)
Lifestyle changes in a fast-paced direction require producers and consumers to be smart about it. Manufacturers are required to provide products with good quality, not only material but also a series of processes applied in the production process. Four aspects, namely awareness about halal assurance certification, commitment to halal certification, availability of resources, and the last aspect is governance, which is the key to these changes. Halal Assurance Certification is one of the indicators that a product meets the quality criteria as halal food that producers must meet. This study aims to determine the awareness and desire of MSMEs to meet the criteria to apply for Halal Assurance Certification. The variables in the questionnaire to be developed following 11 HC criteria, namely halal policy, halal management team, training and education, materials, products, production facilities, written procedures for critical activities, traceability, procedures for handling products that do not meet the criteria, internal audits, management reviews. Data analysis with descriptive statistical tests, using the Pearson Product Moment correlation coefficient to determine the relationship of the data obtained. Administrative requirements are something that needs to be considered. The limitations of human resources with odd job roles are also obstacles in implementing the administrative system. Those criteria are written procedure criteria for critical activities (WPCA), traceability (T), product handling procedures that do not meet the criteria (PH), internal audit (IA), and review management.   The desire of MSMEs to apply for halal certificates is also at a high level. The relationship between consciousness and desire also enters into a strong and moderate relationship in administrative applications. With these conditions, MSMEs assisted by BAZNAS need assistance in applying for halal certificates. Keywords:  halal awareness, halal certification, MSMEs, willingness